Танцы марионеток: [роман] / Елена Михалкова - Михалкова Елена (Детектив-событие, 2009)
Экземпляры: АБ (20180301) / Инвентарный номер: 51745 / Цена: 116.30 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 69 / ББК: 84(2Рос=Рус)6